Phenolic phytochemistry, in vitro, in silico, in vivo, and mechanistic anti-inflammatory and antioxidant evaluations of Habenaria digitata - Almasoudi, Hassan Hussain; Saeed Jan, Muhammad; Nahari, Mohammed H.; Alhazmi, Abdulfattah Yahya M.; Binshaya, Abdulkarim S.; Abdulaziz, Osama; Mahnashi, Mater H.; Ibrar, Muhammad; Zafar, Rehman; Sadiq, Abdul (Frontiers in Pharmacology, 2024)
Excessive and imbalance of free radicals within the body lead to inflammation. The objective of the current research work was to explore the anti-inflammatory and antioxidant potential of the isolated compounds from Habenaria digitata. In this study, the isolated phenolic compounds were investigated for in vitro and in vivo anti-inflammatory potential along with the antioxidant enzyme. The anti-inflammatory and antioxidant potential of the phenolic compounds was assayed via various enzymes like COX-1/2, 5-LOX and ABTS, DPPH, and H2O2 free radical enzyme inhibitory assay. These compounds were also explored for their in vivo antioxidant activity like examining SOD, CAT, GSH-Px, and MDA levels in the brain, heart, and liver. The anti-inflammatory potential was evaluated using the carrageenan-induced pleurisy model in mice. On the basis of initial screening of isolated compounds, the most potent compound was further evaluated for the anti-inflammatory mechanism. Furthermore, the molecular docking study was also performed for the potent compound. The phenolic compounds were isolated and identified by GC-MS/NMR analysis by comparing its spectra to the library spectra. The isolated phenolic compounds from H. digitata were 5-methylpyrimidine-24,4-diol (1), 3,5-dihydroxy-6-methyl-2,3-dihydropyran-4-one (2), 2-isopropyl-5-methylphenol (3), 3-methoxy-4-vinylphenol (4), and 2,6-dimethoxy-4-vinylphenol (5). In in vitro antioxidant assay, the most potent compound was compound 1 having IC50 values of 0.98, 0.90, and 5 μg/mL against ABTS, DPPH, and H2O2, respectively. Similarly, against COX1/2 and 5-LOX ,compound 1 was again the potent compound with IC50 values of 42.76, 10.70, and 7.40 μg/mL. Based on the in vitro results, compound 1 was further evaluated for in vivo antioxidant and anti-inflammatory potential. Findings of the study suggest that H. digitata contains active compounds with potential anti-inflammatory and antioxidant effects. These compounds could be screened as drug candidates for pharmaceutical research, targeting conditions associated with oxidative stress and inflammatory conditions in medicinal chemistry and support their ethnomedicinal use for inflammation and oxidative stress.